The methodology of inheriting the traditional townscape by â€œRe-useâ€ the heritage buildings -Through sharing the case studies in Japan and India - - Ono, Takashi (International Journal of Engineering and Technology, 2018)
This paper is to share the experience in case studies of Japan and India through focusing on the succession of the townscape based on the architectural ‘re-use’. It has tended in Japan in recent years in order to solve the serious issue of the vacant residences in rural area.To begin with, based on the historian Kato’s idea, the architectural manner divides three things; re-use, re-development and restoration/conservation. He insists that the architectural manner and the value of re-use were replaced by two concept of "re-development" or "preservation" that suddenly appeared in modern but still effective.The researching place is selected following three cities; Obuse Town and Azumino City in Japan and Shimla in India. In case of Obuse, we made full use of existing properties of the town by re-using the space which has abandoned so far. And in case of Azumino, we can introduce the re-using building by changing the usage while utilizing the feature of the traditional houses.This paper just introduces the present situation of the architectural re-use of Shimla because we are going on the survey on the site, and the concrete analyzing will be discussed in the next paper.
Keywords: Re-use; Townscape; Heritage building; Conservation; Restore